School closures and effective in-person learning during COVID-19: When, where, and for whom - André Kurmann; Etienne Lalé (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2022)
We match cell phone data to administrative school records and combine it with information on school learning modes to study effective in-person learning (EIPL) in the U.S. during the pandemic. We find large differences in EIPL for the 2020-21 school year. Public schools averaged less EIPL than private schools. Schools in more affluent localities and schools with a larger share of non-white students provided lower EIPL. Higher school spending and federal emergency funding is associated with lower EIPL. These results are explained in large part by regional differences, reflecting political preferences, vaccination rates, teacher unionization rates, and local labor conditions.
Keywords: E24; I24; 330; COVID-19; School closures and reopenings; Effective in-person learning; Inequality